MicroRNA-320a: an important regulator in the fibrotic process in interstitial lung disease of systemic sclerosis - Li, Yiqun; Huang, Jing; Hu, Chaojun; Zhou, Jiaxin; Xu, Dong; Hou, Yong; Wu, Chanyuan; Zhao, Jiuliang; Li, Mengtao; Zeng, Xiaofeng; Liu, Changzheng; Wang, Qian; et al. (Arthritis research & therapy, 2021)
Systemic sclerosis (SSc) is an acquired autoimmune disorder characterized by excessive accumulation of collagen and progressive tissue fibrosis. Although interstitial lung disease (ILD) complicates the majority of SSc patients and is the leading cause of death, its pathogenesis remains largely unclear. In the current study, we aimed to evaluate the role of microRNAs in SSc-ILD. miRNA expression patterns were assessed by miRNA array and real-time PCR from serum and PBMCs of SSc-ILD patients and healthy controls. Bleomycin-induced SSc-ILD mouse model was used to verify the miRNA expression in the lung tissue. The function of miRNAs in pulmonary fibroblasts was assessed using miRNA inhibitors, and mimics. miR-320a was significantly downregulated in both SSc-ILD patients and mouse models. The inhibition or overexpression of miR-320a in human pulmonary fibroblasts significantly affected the protein expression of type I collagen. Luciferase reporter assay, RT-PCR, and western blot analysis identified TGFBR2 and IGF1R as direct targets of miR-320a. Upon TGF-β stimulation, the expression of miR-320a and collagen genes were significantly upregulated. miR-320a, together with its target genes, TGFBR2 and IGF1R, constituted a complex regulatory network, and played an important role in the fibrotic process of SSc-ILD. Investigation of more detailed mechanisms of miR-320a-mediated regulation of collagen expression may provide new therapeutic strategies for SSc-ILD.